A review of adenotonsillar hypertrophy and adenotonsillectomy in children after solid organ transplantation. (November 2018) - Roberts, Jessica; Powell, Jason; Mather, Michael W.; Powell, Steven; Brodlie, Malcolm
Abstract: Objective: Paediatric solid organ transplantation is an increasingly successful treatment. Improved survival is paralleled by increased secondary complications of immunosuppression, including post-transplant lymphoproliferative disease (PTLD). PTLD frequently presents in Waldeyer's lymphatic ring. Adenotonsillar hypertrophy (ATH) is common in children, however in children after transplant, ATH may indicate PTLD. We review the literature on ATH and the role of adenotonsillectomy in children after transplantation. Methods: A comprehensive literature search was performed on the 26 th September 2017 of Ovid Medline (1996–September 2017), Embase (1996–2017) and EBM reviews (Cochrane database of systematic reviews 2005–September 20 th 2017). Results were limited to English language publications within the last 20 years. Abstracts were screened for relevance to PTLD and ATH in the paediatric solid organ transplantation population. Screening of the bibliographies identified further articles. Results: 85 unique articles were screened to yield 18 relevant publications. 10 were retrospective studies and 8 were prospective studies. Conclusion: In children, we report a PTLD incidence of up to 15%, with up to 63% of cases presenting in the head and neck. Histological examination of adenotonsillectomy specimens found PTLD in a mean 5.7% (range 0–39%). We found a lack of prospective studies into this topic and further high quality research is needed. Clinical assessment of ATH in children after transplantation and when to perform a diagnostic adenotonsillectomy remains challenging. Children with ATH warrant prompt further investigation and support from colleagues in transplantation and oncology is required.